EFEK MODERASI KEBIJAKAN DIVIDEN PADA PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Rahmayanti, Kanita Amelia; Wardani, Laila; Burhanudin, Burhanudin (Jurnal Magister Manajemen, 2024)
This research aims to test and analyze the moderating effect of dividend policy on the influence of the Current Ratio (CR), Debt to Equity Ratio (DER), and Return On Equity (ROE) on the share prices of LQ45 Index companies listed on the Indonesian Stock Exchange for the 2018-2022 period. This type of research is causal associative research (cause and effect) with a data collection method, namely a sample survey. Sampling in this study used a purposive sampling technique with certain criteria to obtain a sample of 15 companies with a research period from 2018-2022. The data analysis method used to solve the problems in this research is panel data regression analysis with the help of the EViews 12 program. The results of the research show that Current Ratio (CR) has a positive and not significant effect on stock prices, Debt to Equity Ratio (DER) has a negative and not significant effect on stock prices, Return On Equity (ROE) has a positive and significant effect on stock prices, Dividend Payout Ratio (DPR) is unable to moderate the influence of Current Ratio (CR) on stock prices, Dividend Payout Ratio (DPR) is able to moderate the influence of Debt on Equity Ratio (DER) on share prices, and Dividend Payout Ratio (DPR) are unable to moderate the influence of Return On Equity (ROE) on share prices.